Transcriptional Control of the Production of Aspergillus fumigatus Conidia-Borne Secondary Metabolite Fumiquinazoline C Important for Phagocytosis Protection - Rocha, Marina Campos; Tadini Marilhano Fabri, Joao Henrique; Silva, Lilian Pereira; Figueiredo Angolini, Celio Fernando; Bertolini, Maria Celia [UNESP]; Cunha, Anderson Ferreira da; Valiante, Vito; Goldman, Gustavo Henrique; Fill, Taicia Pacheco; Malavazi, Iran (Oxford Univ Press Inc, 2021)
Aspergillus fumigatus produces diverse secondary metabolites whose biological functions and regulation remain to be understood. Despite the importance of the conidia for this fungus, the role of the conidia-born metabolite fumiquinazoline C (FqC) is unclear. Here, we describe a dual function of the cell-wall integrity pathway in regulating FqC biosynthesis dictated by the MAPK kinase MpkA, which phosphorylates one of the nonribosomal peptide synthetases enzymes of the cluster (FmqC), and the transcription factor RlmA, which directly regulates the expression of fmq genes. Another level of crosstalk between the FqC regulation and the cell physiology is described since the deletion of the stress-responsive transcription factor sebA provokes derepression of the fmq cluster and overproduction of FqC. Thus, we describe a mechanism by which A. fumigatus controls FqC biosynthesis orchestrated by MpkA-RlmA and SebA and hence enabling survival and adaptation to the environmental niche, given that FqC is a deterrent of ameba predation.
Keywords: cell wall integrity pathway; fumiquinazoline C; pkcA; mpkA; rlmA; sebA; amoeba predation